Pengaruh Media Video Edukasi Terhadap Pengetahuan Dan Sikap Ibu Hamil Tentang 1000 HPK (Hari Pertama Kehidupan) - Hidayani, Sri; Harpiana Rahman; Septiyanti; Fairus Prihatin Idris; Haeruddin (Window of Public Health Journal, 2025)
Nearly 800 million people experience chronic malnutrition, and 159 million children under the age of 5 are stunted. Indonesia is included in 17 countries out of 117 countries that currently have 3 nutritional problems, namely stunting (height below standard), wasting (very thin), and overweight (excess weight). To produce healthy and intelligent Indonesian children, the most important initial step to take is to fulfill children's nutrition from an early age, even while still in the womb, or what is known as the First 1000 Days of Life (HPK). This study aims to determine the effect of video media on Knowledge and Attitudes about the First 1000 Days of Life (HPK) in pregnant women. This type of research is quantitative research with a "Pre-Experiment" design with a one-group pretest-posttest design. The sampling technique uses purposive sampling with 38 samples. The population in this study was pregnant women in the first trimester of pregnancy. The data in this study were obtained from filling out questionnaires and observations, and then analyzed using the Mc.Nemar test at a confidence level of 95% (α = 0.05). The results of the study showed that there was a difference in the level of knowledge of pregnant women before being given education, namely 14 (36.8%) had sufficient knowledge and the level of knowledge of pregnant women after being given education was 37 (97.4%). The attitude of pregnant women before education had a positive attitude of 13 (34.2%), and after education had a positive attitude of 33 (86.8%). Based on the results obtained in this study, it is suggested that knowledge and attitudes be improved through video media and that more effective health promotion methods be used. It is crucial for all of us, as healthcare professionals, researchers, and policymakers, to be responsible and committed to this cause, to improve the knowledge and attitudes of pregnant women and, ultimately, maternal and child health.